Electrochemical Biosensing Platform Using Hydrogel Prepared from Ferrocene Modified Amino Acid as Highly Efficient Immobilization Matrix - Qu, Fengli; Zhang, Yi; Rasooly, Avraham; Yang, Minghui (Analytical chemistry (Washington), 2014)
To increase the loading of glucose oxidase (GOx) and simplify glucose biosensor fabrication, hydrogel prepared from ferrocene (Fc) modified amino acid phenylalanine (Phe, F) was utilized for the incorporation of GOx. The synthesized hydrogel displays good biocompatibility and contains a significant number of Fc moieties, which can be considered as an ideal matrix to immobilize enzymes for the preparation of mediator-based biosensors. The hydrogel was studied by scanning electron microscopy, which indicated that it was composed of nanofibers with a diameter of around 50–100 nm and length extended to 1 mm. With the addition of GOx into the hydrogel and by directly dropping the resulting biocomposite onto the electrode surface, a glucose biosensor, that displays good performance due to improved enzyme loading and efficient electron transfer, can be simply constructed. The favorable network structure and good biocompatibility of the hydrogel could effectively avoid enzyme leakage and maintain the bioactivity of the enzymes, which resulted in good stability of the biosensor. The biosensor was utilized for the detection of glucose in blood samples with results comparable to those obtained from the hospital. The hydrogel as a functional component of an amperometric biosensor has implications for future development of biosensors and for clinical applications.